Development of the GridPix detector quad: Talk presented at the 9th Symposium on Large TPCs for Low-Energy Rare Event Detection at Diderot University (Paris, France) on 12 – 14 December 2018. (September 2019) - Bilevych, Yevgen; Desch, Klaus; Fransen, Jean-Paul; van der Graaf, Harry; Gruber, Markus; Hartjes, Fred; van der Heijden, Bas; Heijhoff, Kevin; Ietswaard, Charles; John, Dimitri; Kaminski, Jochen; Kluit, Peter; et al.
Abstract: We have developed the gaseous GridPix detector quad made from four Timepix3 chips. To provide the required charge amplification a Micromegas-like grid has been deposited on the chip surface by MEMS technology. The grid holes are precisely aligned to the chip pixels and have a pitch of 55 μm while the high time resolution of 1.56 ns of the Timepix3 chip enables the precise reconstruction of each individual primary ionization electron in the detector gas. The chip is coated by a high resistivity protection layer to prevent damage by unavoidable discharges. Using the GridPix technology, the full position of the ionization cloud is measured. As such the ultimate resolution of a gaseous detector is achieved, mainly limited by diffusion. The quad has all services located under the detection surface. Multiple quads can be simply joined together to create a large readout plane of a TPC. In this paper we show details about the construction of the quad and the preliminary results from a recent test beam experiment at the ELSA electron beam facility in Bonn.